APRENDIZAJE BASADO EN PROYECTO APLICADO A LA MECÁNICA INDUSTRIAL EN ESTUDIANTES DE BACHILLERATO TÉCNICO - CRUZ SUÁREZ ALBERTO GIOVANNI (2024)
This research project focused on applying Project-Based Learning (PBL) in the educational institution as an innovative teaching strategy for students of Industrial Mechanics at the Simón Bolívar Fiscal High School in the city of Guayaquil. This approach aimed to develop technical skills and motivate students. Project-Based Learning is an innovative teaching strategy in current education. Considering its characteristics as an integrative methodology, it is ideal for developing technical education, in our case, industrial mechanics, where students can develop their knowledge, skills, abilities, and technical competencies. A mixed methodology (quantitative, qualitative) was used. Regarding the research design, it is non-experimental and field-based. Surveys and questionnaires were used for data collection. Statistical methods were applied to manage the data obtained and create tables and graphs. Bibliographic resources were used to gather information, such as books, magazines, websites, legal documents, and the internet, with the aim of thoroughly understanding the numerous theories and perspectives of different authors. Based on the information gathered and the results obtained, the need to permanently use a modern and innovative educational methodology for teaching and learning activities in industrial mechanics in the classrooms and workshops of the institution became evident. Therefore, Project-Based Learning was adopted as the methodology, promoting the development of skills, abilities, teamwork, and technical competencies.